Design, synthesis, spectral analysis & antibacterial activity of thiazol - pyrimidine 5-carboxamide derivatives - GhazalaYasmeen; S.Imam Pasha (IJPAR JOURNAL, 2020)
Several fused heterocycles based on thiazolidinone derivatives were synthesized and characterized using physical properties, elemental analysis, IR and other spectral studies. New ligands i.e. 4-(2-furyl)-6-methyl-2-oxo-thiazol- pyrimidine-5-carboxamidewere synthesized by condensation reaction of thiazolidinone derivatives with phenyl hydrazine in presence of glacial acetic acid. Furthermore the antibacterial of newly synthesized fused heterocyclic compounds was examined against various microbial strains.